Subculturing and Gram staining of blood cultures flagged negative by the BACTEC™ FX system: Optimizing the workflow for detection of Cryptococcus neoformans in clinical specimens - Liu, Lingli; Du, Lijun; He, Shuquan; Sun, Tianshu; Kong, Fanrong; Liu, Yali; Xu, Yingchun (Frontiers in Microbiology, 2023)
Objective: To investigate whether an incubation time of 5 days (Aerobic/F, Anaerobic/F) and 14 days (Myco/F) blood culture bottles is sufficient to prevent false-negative results. Methods: We evaluated 1244 blood bottles (344 patients) defined as negative by the BACTEC™ FX system. We also reviewed published cases and our own cases of bloodstream infection caused by Cryptococcus neoformans and simulated different scenarios, including different inoculation concentrations, bottle types, and clinical isolates. Results: Two bottles (0.16%) were found to contain C. neoformans when subcultured and Gram stained. A 5-day protocol with Aerobic/F bottles was insufficient for the growth of C. neoformans in some cases, and C. neoformans grew better in Myco/F bottles than in Aerobic/F bottles. Conclusion: Subculturing and Gram staining after a 5-day protocol were important for the detection of C. neoformans, and Myco/F bottles should be collected for the blood culture of C. neoformans.